Role of calcium and magnesium administration on sex ratio skewing, follicular fluid protein profiles and steroid hormone level and oocyte transcripts expression pattern in Wistar rat - ARANGASAMY, A; SELVARAJU, S; PARTHIPAN, S; SOMASHEKAR, L; RAJENDRAN, D; RAVINDRA, J P (The Indian Journal of Animal Sciences, 2015)
An attempt was made with 2% calcium and 0.4% magnesium administration to assess the changes in sex ratio skewing in Wistar rat. The results indicated that there was a significant change in sex ratio skewing towards females (11.7% and sex ratio skewed was 1:1.3). There was a significant reduction in serum testosterone levels (P< 0.01) between control (0.35±0.04 ng/ml) and treatment (0.20±0.08 ng/ml) groups and a nonsignificant decrease in follicular fluid. Significant changes were observed in serum T4 level between control (52.32±2.74 nmol/L) and treatment (33.18±3.75 nmol/L) groups. Variation in follicular fluid protein profiles were observed by 2D gel electrophoresis. Differential expression of protein with high molecular weight (52 and 80 kDa) and low pH is not present in treatment group and protein with low molecular weight (10 and 11 kDa) and high pH were observed in treatment group. The expression of transcripts for BMP-15 was 11.5 folds higher and GDF-9 was 3.5 folds higher in treatment group than control. Our results suggested that possible mechanism to favour female offspring could be reduction in serum testosterone and lowering follicular fluid protein molecular weight along with high pH (haemoglobin subunit beta-1 protein (Mr) 15.9 kDa; cytochrome b-c1 complex subunit 8 (Mr) 9.8 kDa; asparagine synthetase (Mr) 64.7 kDa; metal transporter CNNM4(Mr) 87.4 kDa) and increased mRNA expression of BMP-15 and GDF-9 in oocyte.